OC-037 Vitamin D deficiency is common in intestinal failure patients. (28th May 2012) - Culkin, A; Rye, B; Hanson, C
Abstract : Introduction: Vitamin D is essential due to its role in bone health and its immunomodulatory propeties. 1 Patients with intestinal failure (IF) are at risk of Vitamin D deficiency due to inadequate absorption and lack of exposure to UVB light. Deficiency has been demonstrated in IF patients dependent on home parenteral nutrition. 2 We aimed to determine the prevalence of vitamin D deficiency in hospital patients with IF and the efficacy of subsequent prescribed treatment. Methods: All patients admitted to St Mark's Hospital with IF over a 12-month period were included and data on demographics, serum total vitamin D concentration, IF aetiology and vitamin D supplementation prescribed were obtained. If deficiency was identified (≤50 nmol/l) the efficacy of treatment provided was assessed. Descriptive analysis and t-tests were performed. Results: Eighty-four patients were included in the study (42 female, mean age 53±15 years, 92% Caucasian). The aetiology of IF included short bowel (n=30), fistula (n=34), small bowel obstruction (n=13), malabsorption (n=5) and others (n=2). Vitamin D was measured in 76% (n=64) of patients and 75% (n=48) were deficient (mean 41±25 nmol/l, range 9–126). Vitamin D concentrations were lower in men (33.4±15.3 nmol/l) compared to women (49.5±29.5 nmol/l) (p=0.009). No association was demonstrated with age, aetiology of IF, or ethnicity. There was a trend towards reduced Vitamin D and increasing BMI (p=0.187, r 2 =0.028). No seasonal variation was demonstrated between summer (June–November, 42.8±26.5 nmol/l) and winter (December–May, 39.3±21.6 nmol/l) (p=0.57). Only 26% (n=22) of patients had repeat vitamin D concentrations before discharge. There was a significant increase in vitamin D concentrations from 35±22 nmol/l to 44.8±14.3 nmol/l, (p=0.03). Twenty-nine patients received intramuscular Vitamin D at a dose of 300 000 IU. In these patients there was an increase in concentration before (28.4±13.6 nmol/l) and after (42.8±12.7 nmol/l). Due to the small numbers of patients it was not possible to determine the efficacy of the different vitamin D preparations or the effect of the multivitamin preparation used in parenteral nutrition (Cernevit ® ) on serum concentrations. Conclusion: Vitamin D deficiency is common and occurs in three-quarters of IF patients. Male gender was associated with lower concentrations. Robust policies need to be in place for the identification of vitamin D deficiency including the supplementation and monitoring of vitamin D deficiency in patients with IF to ensure adequate serum concentrations are achieved. Competing interests: None declared. References: 1. Michal L, Melamed. 25-Hydroxyvitamin D levels and the risk of mortality in the general population Arch Intern Med 2008;168 :1629. 2. Tee CT, et al. Hypovitaminosis D in patients on long-term parenteral nutrition. Proc Nut Soc 2010;69 :E554.